PERAN MODAL, PENGALAMAN DAN LOKASI USAHA DALAM MEMPENGARUHI TINGKAT PENDAPATAN PEDAGANG KONVEKSI DI PASAR TRADISIONAL SEKETENG - Kayanti, Risa; Sutanty, Marisa (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the factors determining the income level of convection traders in the Seketeng traditional market, which in this study are thought to consist of capital, experience and business location. The type of this study was associative study with quantitative approach. The type of data used was quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 80 convection traders at the Seketeng traditional market. Sample selection used the accidental sampling technique, namely the technique of determining samples by chance. Data were analyzed using multiple linear regression analysis techniques, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and coefficient of determination testing (). The result of this study showed that the capital, experience and business location had a a positive and significant effect on the income level of convection traders in the Seketeng traditional market, either partially or simultaneously. The ability of the capital, experience and business location variables to effected the on the income level of convection traders in the Seketeng traditional market was 42.1%, while the remaining of 57.9% was effected by other variables outside this research model, such as education level, type of business and working hours.